A study on the development of joint tracking-based exercise contents technology for improving the strength of older people - Donggyu Choi; Minyoung Kim; Jongwook Jang (Institute of Advanced Engineering and Science, 2021)
Currently, Korea's population is aging rapidly, and there is a lot of interest in the area of life in old age. Especially, as you get older, your ability to exercise gradually decreases, and you need to exercise continuously for your health. As a result, Korea older people exercise more than welfare powerhouse Japan. However, recently studies show that physical function lags even further. The results are based on a lack of diversity in motion. In Korea, people enjoy walking, hiking, and riding bicycles, but in Japan, there is a difference in the quality of exercise such as muscle-building exercise class, ball exercise, and underwater exercise. The old Korean ways of exercising are all high-intensity sports, but some do not know whether the purpose is for social club purposes. In this paper, real-time joint tracking using a single camera and deep learning was carried out to study the development direction of content that can measure or improve exercise ability to improve actual muscle strength.